ANALISIS WACANA FOUCAULT TENTANG OTENTISITAS AL-QUR’AN: PERSPEKTIF TOSHIHIKO IZUTSU - Muhammad Harfi; Lukmanul Hakim (EL-MAQRA', 2025)
This study analyzes the dominant discourse on the authenticity of the Qur’an in the perspective of Toshihiko Izutsu by employing a semantic approach and Michel Foucault’s power–knowledge framework. This research is a library-based qualitative study that uses Izutsu’s primary works as the main data sources, supplemented by contemporary literature on Orientalism and Qur’anic studies. The findings reveal that Izutsu constructs a dominant discourse affirming the authenticity of the Qur’an through a consistent analysis of internal semantic relations, thereby producing a counter-discourse that challenges the hegemony of classical Orientalist skepticism. This discourse is shaped by Izutsu’s linguistic mastery, cross-cultural intellectual experiences, and broad epistemic horizon, enabling him to interpret the Qur’an objectively and without theological bias. The study also demonstrates that Izutsu’s semantic method functions not merely as a linguistic tool, but as a mechanism of discourse production that establishes an alternative regime of truth within Qur’anic studies. Theoretically, this research strengthens the integration of discourse analysis and semantics in the study of religious texts, while practically it offers a methodological foundation for objective cross-religious research and for developing more critical and interdisciplinary approaches in contemporary Qur’anic studies.